2013
DOI: 10.1016/j.jaap.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The intermediate pyrolysis and catalytic steam reforming of Brewers spent grain

Abstract: reforming produced a significant increase in permanent gases mainly (H2 and CO) with H2 content exceeding 50 vol % at higher reforming temperatures. Bio-oil yield decreased significantly as reforming temperature increased with char remaining the same as pyrolysis condition remained unchanged. The process shows an increase in heating value for the product gas ranging between 10.8-25.2 MJ/m3 as reforming temperature increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 14 publications
9
51
1
5
Order By: Relevance
“…These processes are commercially important as the products can be used in a variety of processes such as combined heat and power (CHP) generation, biofuels and chemicals [2]. Although successful applications have been developed with woody biomass, non-woody biomass can lead to bituminous products which solidify at room temperature [5]. Intermediate pyrolysis enables a diverse range of products such as waste wood, food waste, grass and algae to be utilised [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes are commercially important as the products can be used in a variety of processes such as combined heat and power (CHP) generation, biofuels and chemicals [2]. Although successful applications have been developed with woody biomass, non-woody biomass can lead to bituminous products which solidify at room temperature [5]. Intermediate pyrolysis enables a diverse range of products such as waste wood, food waste, grass and algae to be utilised [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although successful applications have been developed with woody biomass, non-woody biomass can lead to bituminous products which solidify at room temperature [5]. Intermediate pyrolysis enables a diverse range of products such as waste wood, food waste, grass and algae to be utilised [5]. One type of intermediate pyrolysis utilises the pyroformer reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it can be a good potential as gaseous fuel. Furthermore, researchers have reported that gas post-treatments, such as post catalytic reforming (Mahmood et al 2013) have been effective to improve the heating value of the permanent gas. This also indicates a route for further upgrading of the gases as high quality syngas.…”
Section: Gas Analysismentioning
confidence: 99%
“…It is argued that this results from the relatively long residence time and from contact with by-product char which has a catalytic effect (Bridgwater 2012). Recent research has started to investigate the combined effect of prolonged solid residence time and use of char for improving the pyrolysis products (Abu Bakar and Titiloye 2013;Mahmood et al 2013;Ouadi et al 2013;Yang et al 2013a;Yang et al 2013b). It is found that extended involvement of char in the pyrolysis process can lead to an improvement to the quality of the pyrolysis liquid, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…O bagaço de malte seco apresentou baixos percentuais de umidade (3,72%) e cinzas (3,8%) e alto teor de matéria volátil (73,18%). Resultados semelhantes foram observados por Mahmood et al (2012), Carrier et al (2012), Putun et al (1999) e Putun et al (1996) …”
Section: Caracterização Das Biomassasunclassified